From Shantytown to township : an economic study of African poverty and rehousing in a South African city - Maasdorp, Gavin; Humphreys, A.S.B. (Cape Town : Juta and Company Limited, 1975)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: armoede; huisvesting; Afrika; Zuid-Afrika.